Thermo‐elastic analysis of functionally graded multilayered two‐dimensional decagonal quasicrystal plates - Li, Yang; Yang, Lianzhi; Gao, Yang (Zeitschrift für angewandte Mathematik und Mechanik, 2018)
Functionally graded materials have been extensively used as thermal barrier materials and composite laminates to resist high temperatures and reduce the thermal stresses. In this paper, an analytical solution is presented to investigate the response of functionally graded multilayered two‐dimensional thermoelastic decagonal quasicrystal plates. The general solution for a functionally graded simply supported plate with the material properties being assumed to be exponentially distributed along the thickness direction is derived by using the pseudo‐Stroh formalism, and the solution for the corresponding multilayered case is obtained in terms of the propagator matrix method. Numerical results show the influences of functionally graded exponential factor, phonon‐phason coupling coefficient and the thickness of functionally graded quasicrystal layer on the phonon, phason and thermal fields of the plates under the steady‐state thermal load. The obtained results should be useful for future analysis and design of functionally graded layered thermoelastic quasicrystal plates. Functionally graded materials have been extensively used as thermal barrier materials and composite laminates to resist high temperatures and reduce the thermal stresses. In this paper, an analytical solution is presented to investigate the response of functionally graded multilayered two‐dimensional thermoelastic decagonal quasicrystal plates. The general solution for a functionally graded simply supported plate with the material properties being assumed to be exponentially distributed along the thickness direction is derived by using the pseudo‐Stroh formalism, and the solution for the corresponding multilayered case is obtained in terms of the propagator matrix method. Numerical results show the influences of functionally graded exponential factor, phonon‐phason coupling coefficient and the thickness of functionally graded quasicrystal layer on the phonon, phason and thermal fields of the plates under the steady‐state thermal load. The obtained results should be useful for future analysis and design of functionally graded layered thermoelastic quasicrystal plates.